Dynamic restructuring of supported metal nanoparticles and its implications for structure insensitive catalysis - Vogt, Charlotte; Meirer, Florian; Monai, Matteo; Groeneveld, Esther; Ferri, Davide; van Santen, Rutger A.; Nachtegaal, Maarten; Unocic, Raymond R.; Frenkel, Anatoly I.; Weckhuysen, Bert M. (Nature communications, 2021)
Some fundamental concepts of catalysis are not fully explained but are of paramount importance for the development of improved catalysts. An example is the concept of structure insensitive reactions, where surface-normalized activity does not change with catalyst metal particle size. Here we explore this concept and its relation to surface reconstruction on a set of silica-supported Ni metal nanoparticles (mean particle sizes 1–6 nm) by spectroscopically discerning a structure sensitive (CO 2 hydrogenation) from a structure insensitive (ethene hydrogenation) reaction. Using state-of-the-art techniques, inter alia in-situ STEM, and quick-X-ray absorption spectroscopy with sub-second time resolution, we have observed particle-size-dependent effects like restructuring which increases with increasing particle size, and faster restructuring for larger particle sizes during ethene hydrogenation while for CO 2 no such restructuring effects were observed. Furthermore, a degree of restructuring is irreversible, and we also show that the rate of carbon diffusion on, and into nanoparticles increases with particle size. We finally show that these particle size-dependent effects induced by ethene hydrogenation, can make a structure sensitive reaction (CO 2 hydrogenation), structure insensitive. We thus postulate that structure insensitive reactions are actually apparently structure insensitive, which changes our fundamental understanding of the empirical observation of structure insensitivity. Structure insensitivity in catalysis has been empirically observed, but no satisfactory theoretical explanation could be given. By studying different nanoparticle sizes under dynamic catalytic conditions reaction-dependent particle size dependent restructuring was linked to the aforementioned.